Human platelet lysate (hPL) alters the lineage commitment and paracrine functions of human mesenchymal stem cells via mitochondrial metabolism. (March 2022) - Du, Ping; Tao, Xuelian; Liu, Kun; Lin, Jiao; Shi, Yue; Park, Kwideok; Chen, Hsien-Yeh; Lin, Chao-Po; Chang, Junlei; Wong, Raymond CB; Pan, Haobo; Wang, Peng-Yuan
Highlights: Human platelet lysate (hPL) promotes MSCs proliferation in a dose-dependent manner, whilst inhibits cell adhesion and cell spreading. RNA sequencing reveals widespread transcriptome differences between hPL-MSCs and FBS-MSCs. hPL-MSCs downregulate the expression of HIF1A, an important PI3K-Akt pathway downstream transcription factor, in gene and protein levels compared to that of FBS-MSCs. The altered mitochondrial features, lineage commitment, and paracrine functions of hPL-MSCs are all correlated with PI3K-Akt/HIF1A-mediated metabolic changes. Abstract: Emerging evidence indicates that cellular bioenergetics is critical in determining the self-renewal and differentiation of stem cells. Human platelet lysate (hPL) contains abundant proteins, which has been shown to improve self-renewal and osteogenic differentiation of mesenchymal stem cells (MSCs). However, the detailed modulating effect of hPL on MSCs energy metabolism remains unexplored. This study showed that MSCs cultured in hPL displayed a reduced cell size and cell spreading, but an improved proliferation and osteogenic capability compared with cells maintained in fetal bovine serum (FBS). RNA sequencing revealed widespread transcriptome differences between hPL- and FBS-MSCs where the differential expressed genes (DEGs) were enriched mainly in the PI3K-Akt and metabolic signal pathways. We found a significant downregulation of HIF1A (hypoxia-inducible factor 1 alpha) and altered mitochondrial features in hPL-MSCs, indicating a metabolism switch of the hPL-treated cells from glycolysis towards mitochondrial oxidative phosphorylation (OxPhos). It was also demonstrated that hPL-MSCs tend to differentiate towards the aerobic metabolism-demanded osteocytes or adipocytes rather than the anaerobic metabolism-demanded chondrocytes using a differentiation medium. Finally, hPL-MSCs showed an impaired paracrine function where the secreted factors cannot stimulate M2 polarization of THP1 cells and angiogenesis of HUVECs. We concluded that the PI3K-Akt/HIF1A-mediated metabolic state dominated the physiological property and lineage commitment of MSCs in hPL. For the first time, this study demonstrates the molecular mechanism of hPL in the regulation of metabolism and functions of MSCs, which implies the potential of hPL as an efficient biological material for stem cell engineering and regenerative medicine. Graphical abstract: Image, graphical abstract